Sugmentasi Pasar dan Positioning pada Perusahaan Asuransi - M. Nasir; Nuri Aslami (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2022)
The success of an insurance company must be successful in marketing a product contained in an insurance company, and the company must know very well who the target consumers are, therefore a marketing strategy and market segmentation are needed as well as the target market target which is more precise in determining the segment and target market. targeted by the insurance company so that ithe company is able to compete in the market. Keywords: marketing strategy, market segment and positioning